Raton Man part of 'Folsom Man' - Wildermuth, Todd (Raton Range Raton, NM, 1994)
This article is about the Raton Museum's exhibit of "Went to Folsom Looking for a Fossil Skeleton" and the receiving Donations.
Newspaper article + Photograph of Margoree Stockton, Margaret Profaxi, Gene Stockton and Shannon Morrow
Master list item #: 46
File location is in the Raton file Cabinet
Keywords: Stockton, Margoree; Profazi, Margaret -- Office Manager of Bank of New Mexico; Sanchez, Roger -- President of Colfax County Society of Art, History and Archeology; Schwacheim, Carl; Stockton, Gene -- Bank advisory director; Morrow, Shannon -- Raton Museum Director; Bank of New Mexico; Raton Museum; Colfax County Society of Art, History and Archeology; Folsom Man; Traveling Displays; Museum Exhibits; Museum Donations; Museum Funding; Natural History Magazine -- 1927; Community Support; Donations; Raton, New Mexico; 216 South 1st Street